Mentiras aceptadas - Guelbenzu, José María, 1944- (Nuevos tiempos (Madrid, Spain), 2013)
Gabriel, a middle-aged TV screenwriter, divorced father of a preteen, witnesses a traffic accident in the streets of Madrid that causes the death of a child. On the very same day, the lead actor of Gabriel's hit original series dies, thus triggering major changes in Gabriel's life. Shortly thereafter, a shady deal shakes the foundation of the bank where his ex-wife's new husband is the director. Isabel, Gabriel's ex-wife gets wrapped up in the dealings at the bank because her ambition must protect her new husband's reputation and standing, so that this self-made tycoon can provide her with the social status she seeks. Gabriel, concerned about the environment in which his son is being raised, toys with the idea of taking over the care and custody of the boy to remove him from an environment that he considers harmful.